Optimalisasi Peran Guru dalam Pembelajaran PAI pada Generasi Z; Studi Kasus di SMA NU 08 Brangsong, Kabupaten Kendal - Fatah, Zainal (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
This study aims to identify the optimization strategy of Islamic Religious Education (PAI) teachers in educating Generation Z in the digital era, with a case study at SMA NU 05 Brangsong, Kendal Regency. This study employed a qualitative approach to investigate the experiences of teachers and students through observations, in-depth interviews, and document analysis. The study results indicate that PAI teachers face challenges adjusting learning methods to the characteristics of Generation Z, who are digital-native. However, the learning process can run effectively through technology integration, contextual approaches, and ethical and collaborative methods. This study emphasizes the importance of strengthening digital literacy, ongoing teacher training, and collaboration between stakeholders to shape students' religious and moral character amidst the flow of digitalization. These findings provide practical contributions to the development of PAI learning strategies that are adaptive and relevant to the needs of today's generation.